Dapagliflozin, as Add-on Therapy in Type 2 Diabetes Patients, Is Associated With a Reduction in Albuminuria and Serum Transaminase Levels - Benjamin, Silas; Ramanjaneya, Manjunath; Butler, Alexandra E.; Janjua, Imran; Paramba, Firjeeth; Palaki, Jafer; Kubaisi, Aisha Al; Chandra, Prem; Abdalhakam, Ibrahem; Massodi, Nasseer Ahmad (Frontiers in Clinical Diabetes and Healthcare, 2021)
Introduction: SGLT-2 inhibitors are shown to be nephroprotective, slowing progression of nonalcoholic steatohepatitis (NASH) in addition to improving glycemic control in patients with type 2 diabetes (T2D). To date, no real-life clinical data is available on the effect of SGLT-2 inhibitors on albumin-creatinine ratio (ACR) and alanine aminotransferase (ALT) in a Middle Eastern population. Therefore, we evaluated the effect of dapagliflozin (DAPA) on urine albumin-creatinine excretion and ALT when added to standard therapy for T2D. Methods: This is a retrospective study of 40 patients with T2D in whom DAPA was added to their existing anti-diabetic regimen to improve glycemic control. The primary outcomes were changes in serum transaminase level and urine albumin-to-creatinine ratio (ACR). Secondary outcomes include glycosylated hemoglobin (HbA1C) and body mass index (BMI) and reduction in oral hypoglycemic agents and insulin therapy. Results: Whole group analysis showed a reduction in ALT (p<0.0001), AST (p=0.009), ACR (p=0.009) and BMI (p<0.0001) following DAPA treatment. Further sub-group analysis of patients on insulin plus DAPA versus sulfonylurea plus DAPA showed that patients on the insulin and DAPA combination showed a reduction in ACR (p=0.0090), ALT (p=0.0312), BMI (p=0.0007) and HbA1c (p<0.0001). In the sulfonylurea and DAPA combination group, there was a reduction in the sulfonylurea requirement following DAPA therapy (p=0.0116), with reductions in ALT (p=0.0122), AST (p=0.0362), BMI (p=0.0026) and HbA1c (p<0.0001) but no change in ACR (p=0.814). Conclusion: In routine clinical practice, the addition of DAPA to standard medical therapy is safe and beneficial for T2D patients, resulting in reduction of ALT and ACR.